Fungal endocarditis leading to pulmonary embolism and death - Araujo, Gustavo Neves de; Valle, Felipe H.; Freitas, Douglas Dal Mas; Gus, Miguel; Rohde, Luis E. (Clinical and Biomedical Research, 2015)
A 38 year-old male was admitted to the emergency room with fever and hemoptysis in the last 3 weeks. His past medical history included previous intravenous drug usage (20 years before), severe acute pancreatitis in the last year, and steroid therapy for the last 10 months due to presumptive diagnosis of bronchiolitis obliterans organizing pneumonia. The episode of pancreatitis required hospital admission, when the patient received total parenteral nutrition and also had an episode of pneumonia treated with antibiotics.